Teacher Creativity in Implementing Indonesian Language Learning Using Cursive Letter Writing - Khusna Zuhaida; Rakanita Dyah Ayu Kinesti (Universitas Islam Negeri (UIN) Salatiga, 2023)
This qualitative research aims to explore the teacher's creativity in implementing Indonesian language learning through cursive letters at MI Nahdlatul Ulama 01 Purwosari Kudus and its impact. The study involved the school principal, the Class III Indonesian language teacher, and 28 Class III students. Data were collected through interviews, observations, and documentation. The findings revealed that the teacher's creativity in teaching Indonesian language through cursive letters involved the use of a scientific approach and the alternating habituation method accompanied by ice-breaking activities. Media such as posters, whiteboards, and fine notepads were also employed. The positive impacts of this implementation included increased student enthusiasm, improved and neater student writing, and gradual enhancements in learning outcomes for cursive letter writing. However, negative impacts were observed in the prolonged time needed for the process and the perceived difficulty in writing cursive letters, posing a distinct obstacle for students.